The Birth of Grapevine Health A Doctor's Journey to Build Trust and Restore Humanity in Medicine. - Fitzpatrick, Lisa K. (Milton : Productivity Press, 2023)
The COVID-19 pandemic has taught the world many things, but one of the most crucial is the need to communicate tailored health information through trusted messengers effectively. The Birth of Grapevine Health chronicles the experiences of one physician, Dr. Lisa Fitzpatrick, a CDC-trained medical epidemiologist on a mission to deliver trusted health information to the Black community through Grapevine Health, a community and health outreach organization she started with the aim to improve patient engagement and health literacy in underserved communities through the digital delivery of tailored health messages. Fitzpatrick reveals why she began building an organization that, in 2020, appeared tailored for the COVID-19 pandemic long before that crisis unfolded across the globe. Frustrated by the lack of progress in addressing health inequity, Dr. Lisa moved into an under-resourced community to become proximal enough to better understand health inequity and the structural and policy changes needed to address it. She weaves her professional experiences with storytelling and lessons learned into a call to action for healthcare leaders, decisionmakers, and funders to move beyond data collection and shift toward action to focus on health prevention, move our health support further upstream and, ultimately, improve health outcomes for underserved communities. The Birth of Grapevine Health is part memoir, part health equity playbook, and offers a roadmap to actions needed to achieve health equity. At a time when health equity conversations seem ubiquitous, what sets The Birth of Grapevine Health apart is its embrace and integration of community voice. This book delivers deep insights and, at times, uncomfortable advice through the eyes of Black and brown patients and their communities about what it will take to achieve health equity.
Health Communication -- Addressing Health Equity: The Way Forward -- Epilogue -- Notes -- Acknowledgments -- Appendix: Heard on the Street: Examples of Health Misconceptions and Misinformation -- Index
Description based upon print version of record.
Keywords: BUSINESS & ECONOMICS / Leadership; Fitzpatrick, Lisa K; Community health services; Community health services -- Citizen participation; Health literacy